Evaluation and Social Internship Program of IAIN Sultan Thaha Saifuddin Jambi Students: Using Context, Input, Process and Product Model (CIPP Model) - Hurmaini, Muhammad (AT-TA'LIM, 2015)
The purpose of the research is to know the context, input, process and product evaluation on the Social Internship Program (Kukerta) of IAIN Sulthan Thaha Saifuddin Jambi Students by using Participatory Action Research (PAR) system. The research is conducted in four locations of  IAIN Sultan Thaha Saifuddin Jambi students’ Kukerta in first period of 2013; Lubuk Terap, Sengeti Kecamatan Sekernan, unas, and Simpang Tiga Sipin by using questionnaire. All students of Kukerta in these 4 locations, consists of 51 people become the sample of this study. The finding of the study showed that first, context evaluation of PAR system Kukerta programs is actually having many deficiencies and weakness in both determining the needs as well as the purpose of Kukerta program. Therefore, it needs some improvements or revision. Second, input evaluation of  PAR system Kukerta shows some weakness from the students and the internship supervisors/ advisors. Both students and internship supervisors have to be firstly provided by training on  PAR system Kukerta. Third, process evaluation on the program is also lack of the relevant activities towards students’ needs and program realization. Fourth, product evaluation reveals that there is no significant result of the program, physically or non-physically. It can be recommended that the program can be continued with some improvements and revision on its implementation. Copyright © 2015 by Al-Ta'lim All right reserved